The Effect of MKP Fertilizer and Varieties on the Growth and Yield of Okra (Abelmoschus esculentus L.) - Patria Hannyvone, Irene; Yulianti, Fitri; Kalsum, Ummu (Jurnal Agroekoteknologi Terapan (Applied Agroecotechnology Journal), 2025)
This study evaluated the effects of mono potassium phosphate (MKP) fertilizer and okra varieties on plant growth and yield. A randomized complete block design (RCBD) with two factors was employed: MKP fertilizer at four concentrations (0, 6, 9, and 12 g/L) and two okra varieties (Green Okra Naila IPB and Red Okra Zahira IPB). Growth and yield parameters observed included plant height, leaf number, stem diameter, flowering time, fruiting time, harvest time, fruit length, fruit diameter, fruit weight, fruit number, fresh weight, and dry weight. Results indicated that 6 g/L MKP accelerated flowering, fruiting, and harvesting, while 0 g/L produced the highest leaf number at 10 weeks after planting. The Green Okra Naila IPB variety exhibited a longer harvest period but higher yield. The optimal treatment combination was 12 g/L MKP with the Green Okra Naila IPB variety. A significant interaction between MKP fertilizer and variety was found for fruit weight. Keywords: Green okra, red okra, fertilization, variety, yield. Abstrak. Penelitian ini bertujuan untuk menganalisis pengaruh pupuk MKP (Mono Kalium Phosphate) dan varietas terhadap pertumbuhan dan hasil tanaman okra. Penelitian ini menggunakan Rancangan Kelompok Lengkap Teracak (RKLT) dua faktor. Faktor pertama yaitu pupuk MKP yang terdiri dari empat konsentrasi (0, 6, 9, dan 12 g/L air). Faktor kedua yaitu varietas okra yang terdiri atas dua varietas (Okra Hijau Varietas Naila IPB dan Okra Merah Varietas Zahira IPB). Parameter yang diamati meliputi tinggi tanaman, jumlah daun, diameter batang, umur berbunga, umur berbuah, umur panen, panjang buah, diameter buah, berat buah, jumlah buah, bobot segar tanaman, dan bobot kering tanaman. Hasil dari penelitian ini adalah pupuk MKP 6 g/L mempercepat umur berbunga, umur berbuah, dan umur panen, dan 0 g/L memberikan jumlah daun tertinggi pada 10 MST. Okra Hijau Varietas Naila IPB memiliki umur panen lebih lambat namun hasil lebih banyak. Kombinasi perlakuan terbaik diperoleh pada perlakuan pupuk MKP 12 g/L dan Okra Hijau Varietas Naila IPB. Terjadi interaksi antara pupuk MKP dan varietas terhadap parameter berat buah. Kata kunci: Okra hijau, okra merah, pemupukan, varietas, hasil